Seminário Sagrado Coração de Jesus: os padres lazaristas e a formação religiosa em Diamantina-MG 1950-1964 - Oliveira, Michelle Mattar Pereira de (2014)
Our research has conducted an analysis of a Catholic School that used to offer both religious and formal education, the Seminário Provincial Sagrado Coração de Jesus, administered by the Ordem Lazarista (Diamantina - MG), from 1950-1964. The temporal cut adopted in the research is justified by the fact that in 1950 a reform of the seminar physical space was carried out by the Church and insistently published by newspapers of Diamantina, which seems to have been characterized by presenting to the city another institution with regard to the architectural aspect. Besides that, unpublished documents of the Seminar for the period in question were found, which contain important information in order to know the routine of the institution. The study was carried out until 1964 because in that year the Seminar went through changes provoked by the disruption of the Archdiocese of Diamantina with the administration of Lazarist Fathers and also by their consequent expulsion from the Seminary, where they were established since 1867. On what regards the research problem we have tried to understand whether the Seminary of Diamantina had influenced its society as an institution of education and Catholic religious training. Our objectives were to investigate the educational aspects present in the Seminário Provincial Sagrado Coração de Jesus; get to know the Seminar with regard to students, teachers, routines, activities, curriculum and discipline; analyze the representations of the Seminar constructed and disseminated by newspapers. To achieve these goals we have used the following sources: Book of enrollment of students from 1950-1964; Distribution of lessons among teachers; Statute of the Seminar; Bulletin guidance; Papal Documents; Chronicles Book of the second half of 1964; Activities calendar of the Major/Minor Seminary and the curriculum of each discipline taught for both the Major and Minor seminary students; Correspondence sent by the Reverend Rector of the Seminary, and two newspapers, Estrella Polar and Voz de Diamantina. The results reveal that the Seminário Provincial Sagrado Coração de Jesus influenced the city of Diamantina from 1950-1964 concerning the dissemination of Catholic ideals, since the student studying in that institution received a sound education rooted in Catholic precepts.